Dynamic optical coherence tomography algorithm for label-free assessment of swiftness and occupancy of intratissue moving scatterers - Rion Morishita; Pradipta Mukherjee; Ibrahim Abd El-Sadek; Tanatchaya Seesan; Tomoko Mori; Atsuko Furukawa; Shin‐ichi Fukuda; Donny Lukmanto; Satoshi Matsusaka; Shuichi Makita; Yoshiaki Yasuno (Biomedical Optics Express, 2025)
samples demonstrates the feasibility of the method.
Keywords: Optical Coherence Tomography Applications; Optical Imaging and Spectroscopy Techniques; Retinal and Macular Surgery